Rethinking the just war tradition - Brough, Michael W., 1970-; Lango, John W.; Van der Linden, Harry, 1950- (SUNY series, ethics and the military profession., 2007)
"Rethinking the Just War Tradition provides a timely exploration in light of new security threats that have emerged since the end of the Cold War, including ongoing conflicts in the Middle East, threats of terror attacks, and genocidal conflicts within states. The contributors are philosophers, political scientists, a U.S. Army officer, and a senior analyst at the Center for Defense Information. They scrutinize some familiar themes in just war theory from fresh and original angles, and also explore altogether new territory. The diverse topics considered include war and the environment, justice in the ending of war, U.S. military hegemony, a general theory of just armed-conflict principles, supreme emergencies, the distinction between combatants and noncombatants, child soldiers, the moral equality of all soldiers, targeted assassination, preventive war, right authority, and armed humanitarian intervention. This book illustrates how the just war tradition can be rethought and applied today."--Jacket